A Honeycomb‐Layered Na3Ni2SbO6: A High‐Rate and Cycle‐Stable Cathode for Sodium‐Ion Batteries. (28th July 2014) - Yuan, Dingding; Liang, Xinmiao; Wu, Lin; Cao, Yuliang; Ai, Xinping; Feng, Jiwen; Yang, Hanxi
<x xml:space="preserve">Abstract</x> A honeycomb layered Na3Ni2SbO6 is synthesized as a cathode for sodium‐ion batteries. This new host material exhibits a high capacity of 117 mA h g−1, a remarkable cyclability with 70% capacity retention over 500 cycles at a 2C rate, and a superior rate capability with >75% capacity delivered even at a very high rate of 30 C (6000 mA g−1). These results open a new perspective to develop high‐capacity and high‐rate Na‐ion batteries for widespread electric‐energy‐storage applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>